The Creation of Iraq, 1914-1921 - Simon, Reeva S.; Tejirian, Eleanor Harvey, 1938- (Columbia University Press, 2004)
Leading scholars consider Iraq's history and strategic importance from the vantage point of its residents, neighbors (Iran, Turkey, and Kurdistan), and the Great Powers.